2009
DOI: 10.1038/hdy.2009.82
|View full text |Cite
|
Sign up to set email alerts
|

Multiple paternity and sporophytic inbreeding depression in a dioicous moss species

Abstract: Multiple paternity (polyandry) frequently occurs in flowering plants and animals and is assumed to have an important function in the evolution of reproductive traits. Polyandry in bryophytes may occur among multiple sporophytes of a female gametophyte; however, its occurrence and extent is unknown. In this study we investigate the occurrence and extent of multiple paternity, spatial genetic structure, and sporophytic inbreeding depression in natural populations of a dioicous bryophyte species, Sphagnum lescuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 70 publications
2
46
0
Order By: Relevance
“…Sporophyte production has been shown to be resource limited and abortion of sporophytes in an early developmental stage is not uncommon (Hughes, 1979;Stark and Stephenson, 1983;Stark et al, 2000;Ehrlén et al, 2000). A recent study of Sphagnum lescurii showed that females preferentially supported sporophytes with higher heterozygosity in populations with significant spatial genetic structure (Szövényi et al, 2009). If postfertilization selection based on sporophyte heterozygosity occurs in a moss with dwarf males, the level of heterozygosity in the sporophytes would be higher than what is expected from the available male sexual partners (that is, dwarf males on or nearby the mother shoot).…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…Sporophyte production has been shown to be resource limited and abortion of sporophytes in an early developmental stage is not uncommon (Hughes, 1979;Stark and Stephenson, 1983;Stark et al, 2000;Ehrlén et al, 2000). A recent study of Sphagnum lescurii showed that females preferentially supported sporophytes with higher heterozygosity in populations with significant spatial genetic structure (Szövényi et al, 2009). If postfertilization selection based on sporophyte heterozygosity occurs in a moss with dwarf males, the level of heterozygosity in the sporophytes would be higher than what is expected from the available male sexual partners (that is, dwarf males on or nearby the mother shoot).…”
Section: Introductionmentioning
confidence: 87%
“…The life stage that is most likely to suffer from inbreeding depression is the diploid sporophytic phase . The studies that have attempted to address the relationship between heterozygosity and fitness in sporophytes of various bryophyte species have rendered conflicting results, suggesting that inbreeding depression may be present under certain circumstances but not others Szövényi et al, 2009;Perroud et al, 2011;Jesson et al, 2012;McDaniel and Perroud, 2012;Johnson and Shaw 2015). If the level and risk of inbreeding depression varies greatly between different populations, the selection pressure to avoid inbreeding is also expected to differ.…”
Section: Inbreedingmentioning
confidence: 99%
See 3 more Smart Citations